2017
DOI: 10.1111/jai.13281
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight relationships for seven fish species from Marajó Bay, Amazon estuary, northern Brazil

Abstract: Summary Length–weight relationships (LWR) were estimated for seven fish species inhabiting the intertidal mudflats in the Marajó Bay, northern Brazil. A total of 514 specimens were collected quarterly between November 1994 and December 1995 using a beach seine (5 mm mesh size between opposite knots). Slope b of the LWR varied between 2.93 and 3.11, with a mean of 3.02. This study represents the first reference on LWRs for seven species and a new maximum length record for one of these species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In the Pará River Estuary, length-weight relationships of fish species (Loureiro et al, 2017), as well as the reproductive biology of commercial sciaenids are available (Santos et al, 2010;Barbosa et al, 2012). Plagioscion squamosissimus (sciaenidae) reproduces primarily in February/March and August/September (Barbosa et al, 2012), while Plagioscion magdalenae (Sciaenidae) spawns mainly from August to February (Santos et al, 2010).…”
Section: North Brazil Shelfmentioning
confidence: 99%
“…In the Pará River Estuary, length-weight relationships of fish species (Loureiro et al, 2017), as well as the reproductive biology of commercial sciaenids are available (Santos et al, 2010;Barbosa et al, 2012). Plagioscion squamosissimus (sciaenidae) reproduces primarily in February/March and August/September (Barbosa et al, 2012), while Plagioscion magdalenae (Sciaenidae) spawns mainly from August to February (Santos et al, 2010).…”
Section: North Brazil Shelfmentioning
confidence: 99%
“…Knowledge of the richness of marine and freshwater fish fauna in the State of Amapá is still poor and few studies have generated length-weight relationship parameters (LWR) (Silva, Oliveira, Florentino, & Tavares Dias, 2015;Oliveira, Silva, Prestes, & Tavares Dias, 2018) which are essential for the management of fish stocks, knowledge of the ecological behavior of fish species, biomass estimates, and determine fish welfare using the allometric condition factor (Vazzoler, 1996;Froese, 2006;Giarrizzo, Bastos, & Andrade, 2011;Soares, Santos, Mendes, Barthem, & Montag, 2015;Loureiro, Mourão Júnior, & Giarrizzo, 2017;Oliveira et al, 2018). Among such studies only one deeper investigation was conducted, as it evaluated the Maximum Sustainable Yield (MRS) of fishery resources in the Araguari River, and observed that the effort and yield of Characiformes and Siluriformes -target fisheries are above what the environment supports, characterizing it as an overexploited resource (see Oliveira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%